Integrated Genomic Analysis Reveals the Impact of Avermectin on Chromatin Structure and Gene Expression Regulation in Bombyx mori - Yongkang Guo; Tong Zhang; Wei Lu; Dan Liu; Junjie Lao; Na Zhang; Hao Sun; Ling Jia; Sanyuan Ma (Insects)
Avermectin is a widely used insecticide for pest control, such as the Plutella xylostella. Despite its efficacy in pest management, concerns have been raised regarding its effect on non-target species, such as the important economic insect silkworm (Bombyx mori). We aimed to investigate the effects of avermectin application on the 3D genome architecture of silkworm midgut using high-throughput techniques such as high-throughput chromosome conformation capture (Hi-C) coupled with RNA sequencing (RNA-seq) and Assay for Transposase-Accessible Chromatin using sequencing (ATAC-seq). Midgut tissue samples, during the fifth instar and three days, were collected from silkworm larvae fed mulberry leaves (control group) and leaves soaked in avermectin solution for 12 h (experimental group). Our findings revealed that avermectin treatment led to significant changes, including 386 differentially expressed genes (252 up-regulated, 134 down-regulated) and increased chromatin accessibility, particularly those involved in immune response, metabolism, and cellular stress pathways. The Hi-C data revealed more intense spatial interactions in the experimental group, leading to increased expression of detoxification proteins like ABC transporter. This study provides important insights into the molecular basis of pesticide resistance and a foundational basis for further research on the genetic and epigenetic mechanisms of insect stress responses.